Kajian Literatur: Penggunaan Media Audio Visual sebagai Pendukung Pembelajaran di Madrasah Ibtidaiyah - Nurhidayah Nurhidayah; Nurhayati Nurhayati; Dony Ramadan; Ummi Sholehah; Vika Yuniar; Ghina Mubarokah; Ali Iskandar Zulkarnain (STAI YAPIS Takalar, 2026)
This study aims to examine the use of audio-visual media as a learning support in Madrasah Ibtidaiyah and analyze the benefits, effectiveness, and constraints of its application in the learning process. The research uses qualitative methods with library research approach. Data were obtained from various sources of literature, such as scientific journal articles, books, theses, proceedings, and previous research relevant to the research topic. Data collection techniques are carried out through documentation by reviewing, reading, and analyzing various literature related to audio-visual media in learning. Data analysis using qualitative descriptive techniques through the stages of data reduction, data presentation, and conclusion. The results showed that the use of audio-visual media has a positive impact on the process and learning outcomes in Madrasah Ibtidaiyah. Audio visual Media can increase learning motivation, student activity, and learning outcomes because learning materials are presented in a more concrete, interesting, and easy to understand through a combination of sound, image, video, and animation elements. In addition, audio-visual media also support student-centered learning so as to create a more interactive and meaningful learning atmosphere. However, its implementation still faces several obstacles, such as limited facilities and infrastructure, lack of teacher skills in utilizing technology, and relatively longer preparation time. Therefore, it is necessary to support the facilities and increase the competence of teachers so that the use of audio-visual media can be applied optimally in improving the quality of learning in Madrasah Ibtidaiyah.